PENGEMBANGAN DAN VALIDASI METODE ANALISIS PENENTUAN KADAR ASAM TRANEKSAMAT DENGAN PENDERIVATISASI NINHIDRIN DALAM SERUM WAJAH - Nabila Muhsin, Farah
In Indonesia, cosmetics used for skin whitening are commonly used. Tranexamic acid as a whitening agent occurs in a variety of preparations, including facial serum. High concentrations of tranexamic acid in topical preparations can lead to skin irritation. In Indonesia, BPOM regulates the highest concentration of tranexamic acid that is allowed in topical preparations is 3%. Therefore, an analytical method that can measure levels of tranexamic acid is necessary. In this research, a method was developed to measure tranexamic acid levels in facial serum preparations using high performance liquid chromatography (HPLC). The study was started with mobile phase optimization, system suitability testing and validation of analytical methods, including selectivity, linearity, accuracy, and precision. Based on the optimization results, the analysis of tranexamic acid in facial serum samples was carried out by a derivatization process using a 0.2% ninhydrin solution in methanol. In this study, acetonitrile – 20 mM acetate buffer pH 5 (25:75, v/v) was used as mobile phase, with the isocratic method, the stationary phase was an Agilent ZORBAX Eclipse C18 column, the injection volume was 20 ?L, the flow rate was 0.9 mL/minute, and the wavelength 568 nm. The linearity parameter was expressed as a correlation coefficient of 0.999 in the concentration range of 4 – 24 ?g/mL. The limits of detection and quantitation of tranexamic acid were 1.02 ?g/mL and 3.40 ?g/mL, respectively. The recovery value for accuracy was in the range of 97.57 - 101.96 %. In the Intraday and Interday precision test, the relative standard deviations was 1.081 and 1.091 %. The validated analytical method was then used to measure levels of tranexamic acid facial serum on the market with sample levels between 0.703 – 3.082 %.